Diagnosis and Outcome of Tuberculosis of Knee Joint (Gonitis Tuberculosis) with Pulmonary Tuberculosis after Completing Anti-Tuberculosis Therapy: A Case Report - Anita Nur Charisma; Winariani Koesoemoprodjo (Jurnal Respirasi, 2021)
Background: Tuberculosis (TB) in extra-pulmonary organs, such as bone and joint TB, has an incidence rate of 19% of the cases and represents 11-15% of all extra-pulmonary TB. The predilection of bones and joints is the most common predilection with more than 10% of the cases. Gonitis TB is a monoarthritis, chronic progressive, and intermittent disease. Hematogenous spreads through synovial or subchondral or as a focus in the juxta-articular bone. The spread can also occur indirectly from osseous lesions of the epiphyseal bone in adults or metaphysis in children, which causes erosion in the joint space and becomes arthritis.Case: A 19-year-old female with a chief complaint of swelling in the right knee joint accompanied by pain and difficulty in the legs to move and straighten the body. Another complaint was cough with whitish sputum, fever and night sweating, decreased appetite, and loss of body weight. Radiological chest X-ray showed fibro-infiltrates in both hemithoraces and radiological of the right genu, impression like joint effusion and mass density opacity in the popliteal, and suspicious abscess in the soft tissue. GeneXpert MTB/RIF examination of genu tissue and sputum: medium  Mycobacterium tuberculosis (M.Tb) was detected, rifampicin sensitive. Histopathology from the open biopsy showed the tissue consisted of epitheloid-shaped histiocyte cells forming granulomas. Ziehl Neelsen staining of the tissue obtained acid-fast bacillus (AFB).Conclussion: Gonitis TB is a hematogenous spread of M.Tb from infection with a deep primary focus on the joint that is chronic progressive and generally affects one joint. The management can be done by administering anti-tuberculosis and clinical monitoring.